Procedural environmental rights in regional trade agreements: trends, policy drivers and the case for multilateralisation within the World Trade Organization - Bondi, Vyonna Achieng (Department of Public Law, 2025)
The World Trade Organization (WTO) is at the nexus between trade and the environment. The General Agreement on Tariffs and Trade (GATT), as amended in 1994 during the Uruguay Round, in effect established a new treaty structure to govern international trade and commerce. The underlying philosophy under the GATT/WTO regime is that states undertake to enter into mutually reciprocal agreements aimed at tariff reduction and removal of other barriers to trade, while eliminating any form of discrimination. Since the inception of GATT, Article XXIV has facilitated the conclusion of Regional Trade Agreements (RTAs), which constitute an exemption from the Most Favoured Nation (MFN) principle of non-discrimination. Multilateral negotiations within the WTO system have, therefore, been complemented by regionalism. Both trends have come to apparently coexist in the international trading system, raising important questions as to the future of the multilateral trading system. The core principles of non-discrimination underlying the trading system, have also been qualified to the extent that GATT Article XX paragraphs (b) and (g) enables states to ‘discriminate' based on the protection of human health and the environment. Therefore, many RTAs also include substantive environmental rights (SERs) in addition to procedural environmental rights (PERs), namely access to environmental information, public participation in environmental decision-making and access to justice in environmental matters. These three pillars of the Rio Principle 10 function as a mechanism for safeguarding fundamental rights to a clean environment included in RTAs, advancing the objectives of sustainable development, which is also a stated objective of the WTO. In light of the deadlock in multilateral trade negotiations, compounded by the paralysis within the WTO dispute settlement mechanism (DSM), states have increasingly turned to regional trade agreements (RTAs) as alternative frameworks for trade cooperation. However, this shift has largely occurred without sufficient regard for the harmonisation of these agreements, leading to what has been termed the ‘spaghetti bowl' or ‘noodle bowl' phenomenon. This refers to the intricate and often contradictory web of overlapping and diverging legal regimes that now govern international trade. As a result, states are left grappling with conflicting obligations, which complicate the uniform implementation of PER commitments. The lack of coherence across these frameworks exacerbates regulatory fragmentation, impeding legal certainty and fostering inconsistency in the application of trade rules. Thus, states are not only responding variably to the same commitments but are also facing significant challenges in navigating the complexities of these multifaceted and, at times, discordant legal obligations. This legal fragmentation poses substantial risks to the predictability and stability of the international trading system, further undermining the intended goals of PERs within RTAs. In order to ascertain to what degree PER commitments have converged or diverged, the thesis develops an assessment tool comprising key features to analyse the spaghetti bowl of trade agreements and, in particular, PER provisions to derive a typology of PER provisions. The thesis assesses possible avenues for the multilateralisation of PER provisions including the adoption of conditions in preferential trade agreements and the conclusion of plurilateral agreements on PERs, among others.